2022
DOI: 10.1186/s10033-022-00757-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Piston Number on Churning Losses in Axial Piston Pumps

Abstract: Raising the rotational speed of an axial piston pump is useful for improving its power density; however, the churning losses of the piston increase significantly with increasing speed, and this reduces the performance and efficiency of the axial piston pump. Currently, there has been some research on the churning losses of pistons; however, it has rarely been analyzed from the perspective of the piston number. To improve the performance and efficiency of the axial piston pump, a computational fluid dynamics (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A computational fluid dynamics model of an axial piston pump was developed to analyse churning losses. 19 A test stand was built on a computer numerical control (CNC) machine to study the dynamic effect of the annular flow on a rotor. 20 The results showed that the annular flow gap significantly affected the vibration characteristics and stability of the rotor system.…”
Section: Introductionmentioning
confidence: 99%
“…A computational fluid dynamics model of an axial piston pump was developed to analyse churning losses. 19 A test stand was built on a computer numerical control (CNC) machine to study the dynamic effect of the annular flow on a rotor. 20 The results showed that the annular flow gap significantly affected the vibration characteristics and stability of the rotor system.…”
Section: Introductionmentioning
confidence: 99%
“…When the number of pistons and the displacement of the pistons are the same, reducing the pitch radius of the piston hole is the best method to reduce the churning loss. 13 Wei et al used the moving particle semi-implicit (MPS) method to calculate the churning loss of the hydraulic pump, and the results showed that the total churning loss decreased with the decrease of the tilt angle of the swash plate. When the oil content is 70%, the churning loss of the pump is reduced by 57.4%.…”
Section: Introductionmentioning
confidence: 99%